RUSSIAN INTERNET INFRASTRUCTURE IN THE AGE OF DIGITAL SOVEREIGNTY AND INFRASTRUCTURAL COERCION: THE CASE OF TSPU - Kuznetsov, Dmitry (AoIR Selected Papers of Internet Research, 2026)
This paper examines how the Russian state, following its 2022 invasion of Ukraine, accelerated coercive controls over internet infrastructure through the rapid deployment of Technical Measures to Combat Threats (TSPU). Building on Maxigas and ten Oever’s (2023) framework of infrastructural ideologies, the study introduces infrastructural coercion as a crisis-driven strategy, contrasting it with hegemonic models reliant on tacit compliance. The research combines analysis of legislative texts with an examination of sessions from the Conference of Russian Telecom Operators (КРОС, 2018–2024). Findings reveal operators’ strategies to mitigate coercive measures: exploiting legal ambiguities (e.g., license reclassification), adopting phased DPI implementation, and leveraging sanctions-driven import substitution. KROS discourse shifted markedly—from openly mocking “unworkable” laws in 2018 to framing post-2022 challenges as “temporary difficulties” within an optimistic techno-nationalist trajectory. The study challenges state-centric narratives of digital sovereignty by centering infrastructural actors’ agency. It demonstrates that tools like DPI are neither neutral nor inevitable: their adoption reflects ideological priorities, while material constraints expose fissures in state control. Russia’s case illustrates that “great firewalls” can emerge rapidly using existing technologies. By foregrounding implementers’ negotiations, this research advances scholarship on infrastructural governance and the political valence of technical systems.